Análise multivariada aplicada na construção de scores de rendimento dos principais jogadores do futebol mundial - Brigante, Gianpedro Robertto Mella [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
In this work, two methods of multivariate analysis were adopted, Principal Component Analysis and Cluster Analysis, with the aim of analyzing the performance, taking into account variables related to the attack of the main athletes of the five biggest national championships, namely: the Brasileirão Serie A, La Liga, Serie A Italia, Premier League and France Ligue. The Principal Component Analysis method was used to reduce the number of variables and simplify the players’ interpretation, in addition to providing the performance scores of each analyzed athlete. This application was very effective as it managed to extract about 84% of the information from eight correlated variables into two new uncorrelated variables. With this model it was also possible to make Biplot graphs that helped to identify the players who stood out the most in each variable due to the scores obtained. The performance of players by championship was also analyzed, allowing the comparison of these studied competitions. After obtaining the performance scores, a grouping method called Ward’s Method was used, which groups the individuals (athletes) according to their proximity according to the data, then the quality of these groups was observed by the silhouette graph that makes it possible to see if the player is well placed in his group. Making the grouping taking into account only the scores of the two components chosen, it was noticed that it was not possible to find a strong structure of the groups, but the groups were consistent with the interpretations obtained in the Biplot graphs.

Neste trabalho foram adotados dois métodos de análise multivariada, a Análise de Componentes Principais e a Análise de Agrupamentos, com o intúito de analisar o rendimento, tendo em consideração variáveis relacionadas ao ataque dos principais atletas dos cinco maiores campeonatos nacionais, sendo eles: o Campeonato Brasileirão Série A, La Liga, Série A Italia, Premier League e France Ligue. O método de Análise de Componentes Principais foi usado para diminuir a quantidade de variáveis e simplificar a interpretação dos jogadores, além de proporcionar os scores de rendimento de cada atleta analisado. Esta aplicação foi muito efetiva pois conseguiu extrair cerca de 84% da informação de oito variaveis correlacionadas em duas novas variaveis não correlacionadas. Com esse modelo também foi possível fazer gráficos Biplot que ajudaram a identificar os jogadores que mais se destacaram em cada variavel devido aos scores obtidos. Também foi analisado o desempenho dos jogadores por campeonato possibilitando a comparação dessas competições estudadas. Após a obtenção dos scores de rendimento foi usado um método de agrupamento denominado Método de Ward, que agrupa os indivíduos (atletas) conforme suas proximidades de acordo com os dados, depois a qualidade desses grupos foram observadas pelo gráfico da silhueta que possibilita ver se o jogador está bem alocado em seu grupo. Fazendo o agrupamento levando em conta somente os scores das duas componentes escolhidas percebeu-se que não foi possível encontrar uma forte estrutura dos grupos, mas os grupos foram condizentes às interpretações obtidas nos gráficos Biplot.
Multivariate analysis applied in the construction of productivity scores of the main players of world football
Keywords: Soccer; Multivariate analysis; Performance; Principal components; Ward’s method; Futebol; Análise multivariada; Score; Rendimento; Componentes principais; Método de Ward; Análise de agrupamentos; Análise de componente principais